The Guidebook to Molar Endodontics - Peters, Ove A. (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This volume offers readers a pragmatic approach to endodontic therapy for permanent molars, based on up-to-date evidence. All chapters were written by experts in the field, and focus on preparation for treatment, vital pulp therapy, access cavity preparation, root canal shaping, outcome assessment, retreatment, apical surgery, and specific aspects of restorations for root canal-treated molars. The role of micro-CT data in visualizing canal anatomy is compared to cone beam CT, and detailed information on current clinical tools, such as irrigation adjuncts and engine-driven preparation tools is provided. Important steps are illustrated in clinical photographs and radiographs, as well as by schematic diagrams. Tables and check boxes highlight key points for special attention, and clinical pitfalls. Guiding references are provided. Performing molar endodontics is often a daunting prospect, regardless of the practice setting. This is where "Molar Endodontics" is an ideal source of guidance for practitioners. Special devices and recent innovations in apex locators and nickel-titanium instruments have, however, made procedures significantly easier and more practical for non-specialists. This book will help conscientious clinicians to master molar endodontics with well-described and established clinical methods.
Keywords: Dentistry.; elektronické knihy; electronic books